2022
DOI: 10.1002/dac.5127
|View full text |Cite
|
Sign up to set email alerts
|

Generic MGF‐based tight approximation for the error rate analysis

Abstract: The moment generating function (MGF)-based approach is found as more profound as compared with probability density function (PDF)-based counterpart for error rate analysis in any communication system. However, it fails in the case of several modulation schemes with constellation size M, such as M-PSK, M-QAM, and M-PAM schemes among the others, due to the computational complexity of the involved integration. Though authors in the literature suggest alternate analytical expressions to overcome the problem it is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…By utilization of the Equation (07.34.06.0040.01) ) provided in [33], the Meijer-G function in Equation (24) and Equation ( 25) can be expressed in the form of simple functions for the high value of SNR, 𝛾̅ 𝐹𝑆𝑂 → ∞, then Equation ( 24) is derived as…”
Section: Asymptotic Expressionsmentioning
confidence: 99%
See 1 more Smart Citation
“…By utilization of the Equation (07.34.06.0040.01) ) provided in [33], the Meijer-G function in Equation (24) and Equation ( 25) can be expressed in the form of simple functions for the high value of SNR, 𝛾̅ 𝐹𝑆𝑂 → ∞, then Equation ( 24) is derived as…”
Section: Asymptotic Expressionsmentioning
confidence: 99%
“…To strengthen the performance of the system, different techniques are employed, including various digital binary modulation schemes, aperture averaging, and various detection schemes at the receiver. Regarding the effectiveness of relaying systems, a wide range of digital binary modulation approaches has been taken into consideration namely coherent binary phase shift key, on-off keying , binary frequency shift key, and differential phase shift key [24] [25]. Additionally, some authors have considered the aperture averaging technique to enhance performance by minimizing the effects of fading by averaging out intensity fluctuations [26].…”
Section: Introductionmentioning
confidence: 99%
“…In mungbean, some LEA genes viz. VrLEA-55, VrLEA-47, VrLEA-40, and VrLEA-2 were identified by Singh et al (2022), and reported their upregulation under heat stress conditions. Furthermore, genes encoding antioxidant enzymes such as APX, CAT, and SOD have been identified as significant candidates that aid in scavenging reactive oxygen species under stress conditions.…”
Section: Molecular Markers and Candidate Genes Associated With Heat S...mentioning
confidence: 99%